From traditional to digital: Strengthening MSME marketing through online marketplace training in Salatiga - Widyastuti, Emy; Saifudin, Saifudin (Penamas: Journal of Community Service, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in local economic growth, yet many still struggle to market their products online because of limited digital literacy, lack of business training, and unfamiliarity with marketplace platforms. This community service program aimed to strengthen the digital marketing capacity of MSMEs in Salatiga through online marketplace training and mentoring. The participants were 18 MSMEs assisted by LazisMu Salatiga that had not yet used online marketplaces for product marketing. Using a Participatory Action Research approach, the program was implemented through problem identification, training, simulation, marketplace account creation, mentoring, and evaluation. The training introduced online business concepts, marketplace features, digital promotion practices, and strategies to expand market reach. The results showed improvements in digital literacy, digital marketing practices, online sales performance, marketplace utilization, and business competitiveness, with an average increase of 30.2% across five indicators. These findings indicate that marketplace training can support MSMEs’ transition from traditional to digital marketing.